Megafaunal assemblages in deep-sea ecosystems of the Gulf of Cadiz, northeast Atlantic ocean. (May 2022) - Grinyó, Jordi; Francescangeli, Marco; Santín, Andreu; Ercilla, Gemma; Estrada, Ferran; Mecho, Ariadna; Fanelli, Emanuela; Costa, Corrado; Danovaro, Roberto; Company, Joan Batista; Sobrino, Ignacio; Valencia, Javier; et al.
Abstract: Deep-sea ecosystems of the Iberian margin have been widely impacted over the past decades, but the limited knowledge on their biodiversity and functioning limits our ability to contribute to their conservation. So far, in the Gulf of Cadiz, research has mostly been focused on megabenthic assemblages associated to mud volcanoes. However, several other geomorphological structures have remained widely unexplored. Here, by means of a quantitative analysis of 17 video transects conducted between 220 and 980 m depth, we investigated megabenthic assemblages associated to canyons, contouritic channels, contouritic furrows and open slopes. We report the presence of 8 different assemblages, segregated as a result of the different substrates and geomorphologic features. Megabenthic assemblages on hard substrates were characterized by mono or multispecific sponge assemblages. Soft bottoms hosted crinoid beds, pennatulacean meadows and fields of the gorgonian Radicipes gracilis . These results highlight the high diversity of megabenthic assemblages in deep-sea ecosystems of the Gulf of Cadiz and suggest that most of the geomorphological features that remained so far unexplored represent vulnerable marine ecosystems deserving protection and inclusion in future management plans. Highlights: Eight megabenthic assemblages were identified in deep-sea environments of the Gulf of Cadiz. Vulnerable Marine ecosystems were found in all geomorphological features. Sponge assemblages dominated hard substrates and were mostly found on canyon environments. Crinoid beds, pennatulacean and Radicipes gracilis assemblages occupied soft sediment.